Predicting Academic Performance in Mathematics through Online Learning Constructs and Content Proficiencies - Madrilejos , Keith (Journal of Interdisciplinary Perspectives, 2024)
This study explores the evaluation of online distance learning as a significant alternative to traditional education, specifically focusing on its application in Grade 11 mathematics education. The research, conducted in six public senior high schools in Quezon City District IV, employs a descriptive-correlational design and involves 873 Grade 11 students attending online classes. Constructs of online learning, including motivation, access and use of technology, perception, self-directed learning, and online teaching approaches, were examined to understand their impact on mathematics academic performance. The findings revealed that students strongly embraced self-directed learning in the online environment, demonstrating high motivation. Positive feedback was observed towards technology use, online teaching approaches, and the overall perception of online learning. Academic performance was generally satisfactory, with diverse achievements in content-based competencies like Functions and Their Graphs, Mathematics of Investment, and Math Logic. Significant low positive relationships were identified between mathematics academic performance and online learning constructs, as well as content-based competencies. Key predictors of mathematics academic performance included motivation, technology access and use, and online teaching approaches. However, the perception of online learning and self-directed learning did not significantly predict academic performance. These findings contribute to a multiple linear regression model explaining 24% of the variance, highlighting the need to optimize online learning for enhanced mathematics academic performance. Recommendations include students enhancing technology skills and self-directed learning, considering specialized mathematics classes, teachers intensifying instruction in crucial areas, and the Department of Education sustaining the Open High School program while simplifying essential learning competencies in General Mathematics. Future research should explore additional online learning factors for a comprehensive understanding of the subject.